The The Correlation Between Perception, Motivation, and achievement in Blended Learning Implementation - Yuni Kaspirawati; Kurniawati, Nia; Juhana, Juhana (ETERNAL (English, Teaching, Learning and Research Journal), 2023)
: Blended learning method is increasingly recognized, especially after being used as an alternative learning method during the past Covid-19 pandemic. There is a belief that this method also suits learning in other special conditions, such as natural disasters, distance learning, or other conditions that do not allow fully face-to-face learning to be implemented. Moreover, the involvement of technology in blended learning makes this method more appealing for anyone to apply it in modern learning. Given the promising uses of blended learning, all findings regarding its implementation become important. The implementation certainly has impacts on students as the centre of learning. Therefore, it is also important to consider various aspects related to students, including their perceptions and motivations in learning by linking them to their learning achievements. This study investigates the correlation between students' perceptions on blended learning implemented in English teaching at SMAN 1 Sukaresmi, students' motivations in learning English and students' achievements in English subject. The participants of this study are 237 XI grade students of SMAN 1 Sukaresmi. This study employs a questionnaire adapted from the model of Birbal et al. and Gardner's Attitude/Motivation Test Battery, and IBM SPSS Statistics 27 to process the data. The findings confirm that there is a significant and positive correlation between students' perceptions on blended learning implemented and students' achievements in English subject, between students' motivations in learning English and students' achievements in English subjects, and between students' perceptions on blended learning implemented and students' motivations in learning English. Students' perceptions on blended learning implemented in English teaching at SMAN 1 Sukaresmi and students' motivations in learning English simultaneously have a 21.1% influence on students' achievements in English subject. Given the magnitude of the influence exerted, students' perceptions on blended learning and students' learning motivations need to be maintained.